Technology used for offshore mariculture in Spain - Basurco B.; Rodríguez J.; Sarrias F. (Mediterranean offshore mariculture, 2000)
As in other Mediterranean countries, Spain is now observing the rapid expansion of its aquaculture production, particularly in the marine sector. Marine fish farming, which was developed in earth ponds and tanks, is nowadays moving from inshore protected locations to offshore conditions. This paper provides information about the technology in use and being developed in Spain for offshore aquaculture. Although designs used in Spain have originated from a variety of sources, the majority of marine cage farms use 'Polar Cirkel' type plastic ring cages (Corelsa) and most recently, platform structures (MSI). Most cage farms have been located at either inshore or semi-offshore sites and are now being located in increasingly exposed environments. Sea bream and sea bass farms are located along the Mediterranean coast and in the Canary Islands.
Advanced Course of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Mediterranean Offshore Mariculture', 1997/10/20-24, Zaragoza (Spain)